1996
DOI: 10.21273/hortsci.31.5.794
|View full text |Cite
|
Sign up to set email alerts
|

Moringa (Moringa oleifera Lam.): A Versatile Tree Crop with Horticultural Potential in the Subtropical United States

Abstract: The 1990 census of the United States revealed a substantial increase in the ethnic diversity of the American population. Federal dietary guidelines recommend that American consumers double their intake of fresh fruits and vegetables. For quite some time, the ethnic diversity of the population and the associated food patterns have been exposing Americans to a panorama of exotic produce from overseas as well as from selected domestic sources (Greene, 1992). The specialty produce industry in the United States is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 11 publications
0
29
0
8
Order By: Relevance
“…Further investigation found that five citations (Rachmandran et al, 1980;Nautiyal and Venketaraman, 1987;Booth and Wickens, 1988;Palada, 1996;Mughal et al, 1999) …”
Section: Data Recyclingmentioning
confidence: 99%
See 3 more Smart Citations
“…Further investigation found that five citations (Rachmandran et al, 1980;Nautiyal and Venketaraman, 1987;Booth and Wickens, 1988;Palada, 1996;Mughal et al, 1999) …”
Section: Data Recyclingmentioning
confidence: 99%
“…However, the exact nature of the sample analysed is unclear. Inconsistencies in the recycling of information on copper from 1962 (Council of Scientific and Industrial Research, 1962) to 1980 (Rachmandran et al, 1980) and 1980 (Rachmandran et al, 1980) to 1996 (Palada, 1996) have resulted in a 1000-fold increase in copper content being recorded in the literature. Values for copper in 1999 (Mughal et al, 1999) and 1988 (Booth and Wickens, 1988) initially appear to be compensated for due to bases of expression.…”
Section: Used Information From the Wealth Of India (Council Of Scientmentioning
confidence: 99%
See 2 more Smart Citations
“…Moringa oleifera is a pan-tropical tree of great potential value in the tropics due to its nutritional, biomass, water-purification (seeds), agro-forestry, biofumigation (leaves), and medicinal qualities (Palada, 1996;Fahey, 2005). It produces large quantities of seedpods within the first few years of growth.…”
Section: Introductionmentioning
confidence: 99%